IDENTIFIKASI SPASIAL SEBARAN BANGUNAN DI SEMPADAN SUNGAI BESAR KAWASAN DAS SIBERUT - Muhammad Fajri; Adri Frinaldi; Rembrandt Rembrandt (Universitas Tamansiswa Padang, 2023)
This research was conducted in the Siberut Watershed, Mentawai Islands Regency, West Sumatra Province, with the aim of identifying the distribution of buildings, which are located on the boundaries of large rivers in the Siberut Watershed. The data processing method for identifying the distribution of buildings uses spatial analysis methods by digitizing high resolution satellite images using Arc Map 10.8 software and Microsoft Excel software to calculate the number and area of ??land. Based on research results, the border of a large river in the Siberut watershed was found to be 1,297.08 ha, the river passes through two sub-districts and six villages with the predominance of villages from the South Siberian sub-district which has five villages. Based on the results of remote sensing and digitization, there are 525 building points, with a total building area of ??4.62 ha with the largest building position in Muara Siberut Village, with a total of 236 buildings with a total area of ??2.33 ha.